Metagenomic insights into S(0) precipitation in a terrestrial subsurface lithoautotrophic ecosystem - Hamilton, Trinity L.; Jones, Daniel S.; Schaperdoth, Irene; Macalady, Jennifer L. (Frontiers in Microbiology, 2015)
The Frasassi and Acquasanta Terme cave systems in Italy host isolated lithoautotrophic ecosystems characterized by sulfur-oxidizing biofilms with up to 50% S(0) by mass. The net contributions of microbial taxa in the biofilms to production and consumption of S(0) are poorly understood and have implications for understanding the formation of geological sulfur deposits as well as the ecological niches of sulfur-oxidizing autotrophs. Filamentous Epsilonproteobacteria are among the principal biofilm architects in Frasassi and Acquasanta Terme streams, colonizing high-sulfide, low-oxygen niches relative to other major biofilm-forming populations. Metagenomic sequencing of eight biofilm samples indicated the presence of diverse and abundant Epsilonproteobacteria. Populations of Sulfurovum-like organisms were the most abundant Epsilonproteobacteria regardless of differences in biofilm morphology, temperature, or water chemistry. After assembling and binning the metagenomic data, we retrieved four nearly-complete genomes of Sulfurovum-like organisms as well as a Sulfuricurvum spp. Analyses of the binned and assembled metagenomic data indicate that the Epsilonproteobacteria are autotrophic and therefore provide organic carbon to the isolated subsurface ecosystem. Multiple homologs of sulfide-quinone oxidoreductase (Sqr), together with incomplete or absent Sox pathways, suggest that cave Sulfurovum-like Epsilonproteobacteria oxidize sulfide incompletely to S(0) using either O2 or nitrate as a terminal electron acceptor, consistent with previous evidence that they are most successful in niches with high dissolved sulfide to oxygen ratios. In contrast, we recovered homologs of the complete complement of Sox proteins affiliated Gammaproteobacteria and with less abundant Sulfuricurvum spp. and Arcobacter spp., suggesting that these populations are capable of the complete oxidation of sulfide to sulfate. These and other genomic data presented here offer new clues into the physiolo